Is wa a Polysemous Connective? A Case Study of the Qur'anic waw al-'atf - Dror, Yehudit; Borrmann, Kai (Journal for Semitics)
The ways in which parts of a compound statement are related to each other are often easy to understand but hard to explain. A case in point is the “waw of attachment” or al-waw al-'atifa, which associates nouns, verbs and clauses but provides no clues as to its exact interpretation. The particle wa is often interpreted in the target language as “but”, “even if” or “although”. Does this make wa polysemous, comprising related but different meanings? This article argues that wa is part of an incremental reading process that unfolds until the meaning of the text is fully recovered. It shows that the functions of the particle wa can be grouped under four headings: adversative relations where certain features of the items complement each other, additive relations where items are grouped together, consecutive relations indicating the passing of time, and causal relations indicating cause and effect.